Nilai-nilai pendidikan karakter dalam novel Cinta di Langit Qatar karya Defi Taslim - Khasanah, Sefiani Uswatun; Fauzan, Akhmad (Jurnal Pendidik Indonesia, 2025)
This study aims to analyze and describe the character education values contained in the novel Cinta di Langit Qatar by Defi Taslim. The novel was selected as the research source because it portrays the life journey of adolescents filled with moral lessons and character-building experiences. This study employed a descriptive qualitative approach with Zubaedi’s theory of character education as the analytical framework. The data consisted of words, phrases, sentences, and excerpts of narration and dialogue that reflect character education values. Data were collected through literature review and note-taking techniques, while data analysis involved data reduction, data display, and conclusion drawing. The findings reveal twelve character education values reflected in the novel: religiousness, honesty, discipline, hard work, independence, patriotism, friendliness or communicativeness, peace-loving, social care, love of reading, curiosity, and responsibility. Among these, religiosity emerges as the most dominant value, serving as the moral foundation that guides the characters’ actions and decision-making. These findings affirm that literary works can function as effective educational media for the internalization of character values, as moral messages are conveyed contextually through conflicts, dialogues, and the emotional experiences of the characters.